Nonrandom Development of Immunologic Abnormalities after Infection with Human Immunodeficiency Virus: Implications for Immunologic Classification of the Disease - Zolla-Pazner, Susan; Don C. Des Jarlais; Friedman, Samuel R.; Spira, Thomas J.; Marmor, Michael; Holzman, Robert; Mildvan, Donna; Yancovitz, Stanley; Mathur-Wagh, Usha; Garber, Jonathan; El-Sadr, Wafaa; Cohen, Henry; et al. (Proceedings of the National Academy of Sciences - PNAS, 1987)
Blood specimens from 165 intravenous drug users who were seropositive for the human immunodeficiency virus (HIV), from 158 seropositive homosexual men with lymphadenopathy, and from 77 patients with acquired immunodeficiency syndrome (AIDS) were assessed immunologically. Immunologic parameters were analyzed by the Guttman scalogram technique to determine if immunologic abnormalities occurred in a nonrandom pattern. The following four patterns emerged: (i) seropositivity for HIV with no immunologic abnormalities; (ii) seropositivity for HIV with a depressed T4/T8 cell ratio; (iii) seropositivity with a depressed T4/T8 cell ratio and T4-cell depletion; and (iv) seropositivity with a depressed T4/T8 cell ratio, T4-cell depletion, and lymphopenia. Ninety-two to 100% of subjects in each of the three groups of patients were found ``to scale'' because the abnormalities occurred in the cumulative, ordered fashion described. This nonrandom occurrence of abnormalities indicates an ordered progression of immunologic abnormalities in individuals infected with HIV, a finding useful in the staging of both symptomatic and asymptomatic HIV-seropositive subjects.